1990
DOI: 10.1116/1.576995
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of titanium nitride by x-ray photoelectron spectroscopy and Rutherford backscattering

Abstract: X-ray photoelectron spectroscopy (XPS) spectra have been obtained for TiNx, with x=0.25, 0.50, and 1.0, as determined by Rutherford backscattering (RBS) analyses, and with no detectable oxygen content. We find the shape of the Ti 2p transition to be strongly dependent upon the nitrogen content, and interpret the spectrum as a mixture of Ti and TiN. TiN1.0 samples with varying oxygen content were also examined, and the oxygen content serves to increase the background step in the Ti 2p transition. Angle resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(25 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…The binding energy of the XPS O 1s signal indicated that most if not all of the oxygen was bound to carbon, that is, in organic molecules adsorbed on the very surface from air exposure. However, the formation of a small amount of titanium oxide (or oxygen dissolved in the nitride) cannot be excluded [3436]. The presence of large amounts of nitrogen in the form of a titanium nitride constitutes a markedly different surface chemistry compared to the other groups.…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy of the XPS O 1s signal indicated that most if not all of the oxygen was bound to carbon, that is, in organic molecules adsorbed on the very surface from air exposure. However, the formation of a small amount of titanium oxide (or oxygen dissolved in the nitride) cannot be excluded [3436]. The presence of large amounts of nitrogen in the form of a titanium nitride constitutes a markedly different surface chemistry compared to the other groups.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, XPS VB of ion-implanted ceramic sample prepared at higher fluence shows the presence of additional features: the subbands located at ∼16 and 0.5 eV. The energy position of these features is close to those of TiN x [19] and can be attributed to N 2s and Ti 3d-subbands. (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…This effect can be related to the presence of oxidized titanium, created by the exposure of the sample to air, after that the wafer is removed from the reactor. The Ti 2p peak typical of TiN [17] is clearly present at 455 eV (Fig. 6), and a shoulder centered around 458 eV is present as well.…”
Section: A Atomic Layer Deposition Coatingmentioning
confidence: 93%